The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/saje.12235
|View full text |Cite
|
Sign up to set email alerts
|

Bank Income Diversification, Asset Correlation and Systemic Risk

Abstract: This paper explores whether the asset correlations among the non‐interest activities of banks are the key causes for enhancing the bank diversification‐systemic risk nexus. Our empirical evidence indicates that banks' income diversification significantly raises systemic risk. After removing those banks with high asset correlations, the effect of individual banks' diversification on banking systemic risk turns insignificant or even inverse. The results show that high asset correlations among banks could introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…For example, several studies have investigated whether bank risk is affected by corporate governance mechanisms such as board diversity (Arango and Gaitan, 2021; Abou-El-Sood, 2021; Kinateder et al , 2021). Some studies have looked at the impact of bank strategies such as geographic diversification (Le et al , 2020; Le et al , 2019) and income diversification (Lee et al , 2020) or foreign ownership (Lee and Hsieh, 2014; Le, 2021).…”
Section: Brief Overview Of the Literaturementioning
confidence: 99%
“…For example, several studies have investigated whether bank risk is affected by corporate governance mechanisms such as board diversity (Arango and Gaitan, 2021; Abou-El-Sood, 2021; Kinateder et al , 2021). Some studies have looked at the impact of bank strategies such as geographic diversification (Le et al , 2020; Le et al , 2019) and income diversification (Lee et al , 2020) or foreign ownership (Lee and Hsieh, 2014; Le, 2021).…”
Section: Brief Overview Of the Literaturementioning
confidence: 99%
“…Nevertheless, the empirical findings in the literature do not reach a consensus about the impact of business diversification on banks' risks or performance. For instance, some studies indicated that business diversification positively affects banks' risks and performance (e.g., Ferreira et al, 2019); Lee et al, 2020;Uddin et al, 2021;Addai et al, 2022;Alouane et al, 2022;Antao and Karnik, 2022). On the other hand, Business Diversification and Banks' Performance: The Moderating Role of Credit and Liquidity Risk (Empirical Study)…”
Section: Introductionmentioning
confidence: 99%
“…Bank-Specific Indicators In our model we control for the bank characteristics that may affect the impact of bank diversification on capital, risk, efficiency and profitability. Consistent with the prior literature (Abuzayed et al,(2018), Paltrinieri et al (2020), Moudud-Ul-Huq et al, (2019), Meng et al, (2017), Luu et al, (2019) and Lee et al, (2019)), we account for the bank-specific indicators: size, liquidity, intermediation ratio and lending specialization.…”
Section: Non-interest Income = Fee and Commissions Income + Trading Income + Other Operating Income Net Operating Income = Non-interest Imentioning
confidence: 92%
“…However, Ferreira et al, (2018) assess a sample of Brazilian banks and find evidence that revenue diversification is directly connected with risk and positively, but insignificantly, connected with performance. Also, Lee et al, (2019) examine the effect of asset correlation on the relationship between income diversification and risk and their findings indicate that although the relationship is positive, it could be inverted because of asset correlation.…”
Section: Bank Diversification and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation